НОРМАТИВНА РЕГЛАМЕНТАЦІЯ СТРОКІВ ЗАТРИМАННЯ ТА ТРИМАННЯ ПІД ВАРТОЮ ЗА КРИМІНАЛЬНИМ ПРОЦЕСУАЛЬНИМ ЗАКОНОДАВСТВОМ КРАЇН ЄВРОПИ, США ТА ВЕЛИКОБРИТАНІЇ - Кушнєрьов, Віталій Миколайович (SUPREMANCE OF LAW, 2016)
The article analyzes the criminal procedure legislation of Europe, the USA and the United Kingdom in terms of determining the terms of detention and detention. It is determined that the CPC of different states defines the terms of detention and detention in different ways. The vast majority of CPC in foreign countries stipulate that the period of detention may be from 12 to 72 hours, in some cases it may be more or less. Detention can last in most cases from 2 to 12 months. However, there are countries whose CPC provides for detention for more than 1 year during a pre-trial investigation. It has been argued that limiting the pre-trial investigation and trial to 8-12 months, which is mutually exclusive, restricts individuals’ rights to a fair trial, and this can lead to poor quality and violation of legal evidence-gathering procedures. The author proved that the terms of detention and detention in Ukraine correspond to the provisions of most CPC of leading foreign countries.